ANALISIS PENGARUH FITUR STRES KERJA PADA KEPUASAN KERJA DENGAN KECERDASAN EMOSIONAL SEBAGAI VARIABEL PEMODERASI (Studi pada karyawan PT. Bank Tabungan Negara Cabang Surakarta) - Raharjo, Adnan Agus (Riset Manajemen & Akuntansi, 2014)
The main objective of this study was to determine the effect of a variable occupational stress features on job satisfaction of employees with variable moderated by emotional intelligence. The population in this study were 40 employees PT. Bank Tabungan Negara branch office Surakarta and they were taken all to be the subject of the research. Analytical methods used are Moderated Regresion Analysis. The results of this study are as follows. First, physiological stress did not significantly effect job satisfaction. Second, psychological stress have a negative influence on job satisfaction. Third, stress is a significant physiological effect on job satisfaction with emotional intelligence and moderated by the Fourth, affect psychological stress on job satisfaction and not moderated by moderation emotional intelligence.